Modernism's other work the art object's political life - Siraganian, Lisa. (New York ; Oxford : Oxford University Press, 2012)
This title considers writings by Gertrude Stein, Wyndham Lewis Elizabeth Bishop, Amiri Barka, and others, to challenge deeply held critical beliefs about the meaning - in particular the political meaning - of modernism's commitment to the work of art as an object detached from the world.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: American literature -- 20th century -- History and criticism; Modernism (Literature) -- United States; Art in literature; Art objects in literature; Art and literature -- United States -- History -- 20th century; Art -- Political aspects -- United States -- History -- 20th century